Antiplatelet therapy adjustment improved the radiomic characteristics of acute silent cerebral infarction after stent-assisted coiling in patients with high on-treatment platelet reactivity: A prospective study - Li, Wenqiang; Wang, Anxin; Ma, Chao; Wang, Yanmin; Zhao, Yapeng; Zhang, Yisen; Wang, Kun; Zhang, Ying; Wang, Yang; Yang, Xinjian; Liu, Jian; Liu, Xianzhi (Frontiers in Neuroscience, 2023)
Background: We aimed to investigate the effects of high on-treatment platelet reactivity (HPR) and antiplatelet therapy adjustment on high-risk radiomic features in patients with antiplatelet therapy adjustment on acute silent cerebral infarction (ASCI) who had unruptured intracranial aneurysms (UIA) after stent placement. Methods: This single-institution study prospectively included 230 UIA patients who had ACSI after stent placement in our hospital between January 2015 and July 2020. All patients underwent magnetic resonance imaging with diffusion-weighted imaging (MRI-DWI) after stent placement and 1,485 radiomic features were extracted from each patient. The least absolute shrinkage and selection operator regression methods were used for selection of high-risk radiomic features associated with clinical symptoms. In addition, 199 patients with ASCI were classified into three groups: controls without HPR (n = 113), HPR patients with standard antiplatelet therapy (n = 63) and HPR patients with antiplatelet therapy adjustment (n = 23). We compared high-risk radiomic features between three groups. Results: Of the patients who had acute infarction after MRI-DWI, 31 (13.5%) exhibited clinical symptoms. Eight risk radiomic features associated with clinical symptoms were selected, and the radiomics signature exhibited good performance. In ASCI patients, compared with controls, the radiomic characteristics of ischemic lesion in HPR patients were consistent with the following high-risk radiomic features associated with clinical symptoms: higher gray-level values, greater variance in intensity values, and greater homogeneity. However, the adjustment of antiplatelet therapy in HPR patients modified the high-risk radiomic features, which showed lower gray-level values, less variance in intensity values, and more heterogeneous texture. The radiomic shape feature of elongation showed no notable difference between three groups. Conclusions: Adjustment of antiplatelet therapy might reduce the high-risk radiomic features of UIA patients with HPR after stent placement.